Positive perceptions of green and open space as predictors of neighbourhood quality of life: implications for urban planning across the city region. Issue 4 (21st March 2019) - Douglas, Owen; Russell, Paula; Scott, Mark
Abstract : The provision of green and open space in the face of wider development pressure is a key urban challenge. Despite this, few studies have critically investigated the quality of life implications of such provision. This paper focuses on perceptions of built environment factors and their influence on neighbourhood quality of life. Data are drawn from a household survey questionnaire completed by 483 residents living in three neighbourhoods in Dublin, Ireland – an inner city neighbourhood, a suburb and a peri-urban settlement. Positive perceptions of green and open space were identified as important predictors of high levels of neighbourhood satisfaction, surpassed only by dwelling characteristics. This suggests that development strategies which fail to provide for properly planned green and open spaces may be detrimental to neighbourhood quality of life. Furthermore, the results suggest a need for design solutions which consider neighbourhood typology in achieving improved neighbourhood quality of life.